USE OF LEARNING MANAGEMENT SYSTEM ILIAS IN TEACHING TECHNOLOGIES FOR INTENDING TEACHERS OF SECONDARY AND VOCATIONAL EDUCATION - Shymkova, Iryna; Tsvilyk, Svitlana; Hlukhaniuk, Vitaliі; Solovei, Viktor; Harkushevskyi, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The purpose of the article is to substantiate the features of e-learning technologies of materials for intending teachers of secondary and vocational education through the use of available learning management system ILIAS.The web-based learning management system ILIAS is used to develop e-learning materials, manage and disseminate multimedia materials in an online educational environment. The ILIAS system is available, free of charge and designed to manage learning resources as part of integrated systems and e-learning. The independence of the international project ILIAS and its support by many European universities as well as IT organizations are the basis for use and development in the training of intending teachers of secondary and vocational education.While researching the given issue, we have used theoretical and empirical research methods, i.e. analysis and synthesis to clarify the basic concepts and categories of computer-based education; conceptual and comparative analysis of curricula and programs, psychological and pedagogical, scientific and methodical literature as well as the materials of scientific and practical conferences on the problem of research and advanced pedagogical experience, comparing traditional and computer-oriented approaches in teaching technology. We have also used the methods of identifying patterns and drawing conclusions on the given issue.The use of web-based management system ILIAS in the teaching of construction materials technology contributes to the formation of professional competencies of intending teachers of secondary and vocational education, manifested in the ability to integrate knowledge of different technologies, make sound technical decisions and implement them in virtual reality; selection of technological processes, planning, forecasting and evaluation of technology efficiency; perception of computer models of technological processes.